2022
DOI: 10.3390/ijms23169396
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Metal-Organic Frameworks MIL-101(Cr)

Abstract: MIL-101(Cr) is one of the most well-studied chromium-based metal–organic frameworks, which consists of metal chromium ion and terephthalic acid ligand. It has an ultra-high specific surface area, large pore size, good thermal/chemical/water stability, and contains unsaturated Lewis acid sites in its structure. Due to the physicochemical properties and structural characteristics, MIL-101(Cr) has a wide range of applications in aqueous phase adsorption, gas storage and separation, and catalysis. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 199 publications
2
39
0
Order By: Relevance
“…Considering this, FeCuBTC can be used for practical applications. Water molecules can easily bind to the available sites of CuBTC and subsequently attack the Cu–O coordination bond, displacing the ligands through hydrolysis and resulting in the structural collapse of the MOF. , Misra co-workers reported that structural collapse after the exposure of CuBTC to water for 2 h resulted in a 93.3 and 93.5% reduction in the specific surface area and pore volume, respectively . Fan et al also reported the irreversible degradation of CuBTC at 90% RH, which led to a reduction in the adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Considering this, FeCuBTC can be used for practical applications. Water molecules can easily bind to the available sites of CuBTC and subsequently attack the Cu–O coordination bond, displacing the ligands through hydrolysis and resulting in the structural collapse of the MOF. , Misra co-workers reported that structural collapse after the exposure of CuBTC to water for 2 h resulted in a 93.3 and 93.5% reduction in the specific surface area and pore volume, respectively . Fan et al also reported the irreversible degradation of CuBTC at 90% RH, which led to a reduction in the adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…All adsorption experiments were performed in dark glasses without light to prevent possible reactions related to the photocatalytic process. Equilibrium studies of CR and TFT adsorption on MIL-101 (Cr) and nano-MIL-101 (Cr) were performed using variables such as contact time (5-240 min), initial dye concentrations (25-500 mg L À 1 ), initial pH of the solution (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The pH of the suspension was adjusted by dropwise addition of HCl and NaOH (0.1 mol L À 1 ) solutions.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…25−27 Besides, MIL-101 has crystalline water molecules at the end of its molecular structure, which can be removed under high temperature or vacuum conditions, causing MIL-101 to have unsaturated metal sites (Lewis acidic sites), and the unsaturated metal sites can strongly coordinate with the carboxyl group. 28 Thus, using MIL-101 as a support to combine with a carboxyl-functionalized ionic liquid is an ideal approach to preparing a solidsupported ionic liquid catalyst and will provide a good platform to study the deactivation mechanism of solidsupported ionic liquids in the catalytic process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides, a suitable carrier is also important for the stability of an immobilized ionic liquid. Recently, MIL-101 (Matérial Institut Lavoisier), which has large accessible mesoporous cages of 2.9 and 3.4 nm, a large Brunauer–Emmett–Teller (BET) surface area of 3100–4000 m 2 ·g –1 , and high hydrothermal/chemical stabilities, has been applied as the carrier to immobilize active components. Besides, MIL-101 has crystalline water molecules at the end of its molecular structure, which can be removed under high temperature or vacuum conditions, causing MIL-101 to have unsaturated metal sites (Lewis acidic sites), and the unsaturated metal sites can strongly coordinate with the carboxyl group . Thus, using MIL-101 as a support to combine with a carboxyl-functionalized ionic liquid is an ideal approach to preparing a solid-supported ionic liquid catalyst and will provide a good platform to study the deactivation mechanism of solid-supported ionic liquids in the catalytic process.…”
Section: Introductionmentioning
confidence: 99%